2017
DOI: 10.5505/tjtes.2017.41196
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Interosseous Flap versus Reverse Adipofascial Radial Forearm Flap For Soft Tissue reconstruction Of Dorsal Hand Defects

Abstract: BACKGROUND: Our objective was to compare the outcomes of dorsal hand defect reconstruction using a posterior interosseous artery flap (PIAF) and a reverse adipofascial radial forearm flap (RARFF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 13 publications
(23 reference statements)
1
18
0
1
Order By: Relevance
“…[36] As to the donor site scar, patient and parent satisfaction is at an acceptable level in our series and to support this point; it has been reported in the literature that PIO flap is an acceptable option according to the other flap alternatives in which the forearm is used as a donor site. [29] Although there have been reports of temporal motor paralysis due to posterior interosseous nerve damage in the literature, no patient in our series had a wrist drop or similar complication due to a PIN wound.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…[36] As to the donor site scar, patient and parent satisfaction is at an acceptable level in our series and to support this point; it has been reported in the literature that PIO flap is an acceptable option according to the other flap alternatives in which the forearm is used as a donor site. [29] Although there have been reports of temporal motor paralysis due to posterior interosseous nerve damage in the literature, no patient in our series had a wrist drop or similar complication due to a PIN wound.…”
Section: Discussionmentioning
confidence: 55%
“…It has been reported that the planning of the flap skin island to reach the 1/3 distal of the forearm would reduce venous congestion. [29] Sonmez et al reported an alternative solution for venous congestion in a superficial vein anastomosis added to the PIO flap. [30] Furthermore, Nikkhah et al reported in his study that small technical manoeuvres had been conducted for the safe removal of the flap.…”
Section: Discussionmentioning
confidence: 99%
“…9 The venous drainage is carried out through the venae comitentes of the radial artery. 10 In our study we report our experience of reverse radial forearm flap on various defects of hand and wrist without necessitating the use of a option in all these cases. Allen's test was performed preoperatively to confirm the continuity of palmar arch.…”
Section: Introductionmentioning
confidence: 95%
“…Many options have been described to repair these defects and aim to preserve the function and maintain the native color and texture. (Akdag, Yildiran, Sutcu, & Karamese, ; Karamese, Akatekin, Abac, Koplay, & Tosun, ; Liu, Wang, Li, & Du, ; Rehim, Kowalski, & Chung, )…”
Section: Introductionmentioning
confidence: 99%